Beat the cheat: tendencies of academic misconduct and teachers’ interventions - Aspiras, Lauro Santiago; Aspiras, Emma Daynos (Institute of Advanced Engineering and Science, 2025)
This research employed an explanatory sequential mixed-methods approach, integrating quantitative and qualitative techniques across two phases to explore the prevalence of academic misconduct (AM) and the interventions implemented by educators. Data were gathered from randomly selected students and purposively chosen teachers using structured and semi-structured questionnaires, based on specific criteria. The findings revealed significant occurrences of AM among students, including practices such as plagiarism, copying from websites, and sharing quiz answers via social media. Teachers also reported these behaviors, highlighting the multifaceted motivations behind students’ engagement in AM. In response to these challenges, educators implemented a range of interventions. These included confirmatory communication through phone calls and text messages, the introduction of gamified learning activities, constructive feedback on plagiarized work, and supportive outreach via private messages. In some cases, home visits were conducted to reinforce accountability. The study identified four key outcomes of these interventions: student compliance with academic integrity measures, acceptance of the consequences of misconduct, receptivity to feedback, and the phenomenon known as “Ningas Kugon” mentality, which describes inconsistent or transient changes in student behavior. Hence, this inquiry provides valuable insights into the dynamics of AM and the effectiveness of various educator interventions.